Inhibiting doping in sports: deterrence is necessary, but not sufficient. Issue 1 (2nd January 2017) - Bowers, Larry D.; Paternoster, Raymond
Abstract: The use of performance-enhancing drugs is a significant problem in sport. It cheats clean athletes of their hard-earned rewards from perfecting their skills though dedication and hard work. It defrauds fans by substituting a distorted playing field for a true competition. Anti-doping agencies have been charged with enforcing drug policies, primarily through the use of drug testing programs. We propose that drug testing, while important, is not sufficient to achieve deterrence. Engaging the principles of perceptual deterrence and development of a moral community of athletes can greatly enhance compliance with rules.